The contribution of the SafeWAVE EU project to the future development of ocean energy - Juan Bald; Galparso Ibon; Mandiola Gotzon; De Santiago Iñaki; Menchaca Iratxe; C. Uyarra María; Pouso Sarai; Uriarte Ainhize; Muxika Iñigo; Sobradillo Beatriz; Vinagre Pedro; Mchado Inês; et al. (International Marine Energy Journal)
The development of marine renewable energies and wave energy (WE) in particular, are vital components of sustainable ocean governance and the transition towards a low-carbon economy. In a new industry like marine renewable energy (MRE), and Wave Energy (WE) in particular, time-consuming procedures linked to uncertainty about project environmental impacts, the need to consult with numerous stakeholders and potential conflicts with other marine users appear to be the main obstacles to consenting WE projects. These are considered as non-technological barriers that could hinder the future development of WE in EU. Through three different strategies (environmental demonstration strategy, consenting and planning strategy and education and public engagement strategy), the aim of the SafeWAVE project has been to contribute to overcome these barriers through the knowledge and tools developed during the project life.